Region-specific up-regulation of oxytocin receptor binding in the brain of mice following chronic nicotine administration. (23rd July 2015) - Zanos, Panos; Georgiou, Polymnia; Metaxas, Athanasios; Kitchen, Ian; Winsky-Sommerer, Raphaelle; Bailey, Alexis
Highlights: Nicotine administration increases amygdalar oxytocin receptor binding. Chronic nicotine does not alter oxytocin receptor binding in the striatum. Oxytocin may be a potential target for the treatment of nicotine addiction. Abstract: Nicotine addiction is considered to be the main preventable cause of death worldwide. While growing evidence indicates that the neurohypophysial peptide oxytocin can modulate the addictive properties of several abused drugs, the regulation of the oxytocinergic system following nicotine administration has so far received little attention. Here, we examined the effects of long-term nicotine or saline administration on the central oxytocinergic system using [ 125 I]OVTA autoradiographic binding in mouse brain. Male, 7-week old C57BL6J mice were treated with either nicotine (7.8 mg/kg daily; rate of 0.5 μl per hour) or saline for a period of 14-days via osmotic minipumps. Chronic nicotine administration induced a marked region-specific upregulation of the oxytocin receptor binding in the amygdala, a brain region involved in stress and emotional regulation. These results provide direct evidence for nicotine-induced neuroadaptations in the oxytocinergic system, which may be involved in the modulation of nicotine-seeking as well as emotional consequence of chronic drug use.